Altered Expression of Complement Regulatory Proteins CD35, CD46, CD55, and CD59 on Leukocyte Subsets in Individuals Suffering From Coronary Artery Disease - Mishra, Nitesh; Mohata, Madhav; Narang, Rajeev; Lakshmy, R.; Hazarika, Anjali; Pandey, R. M.; Das, Nibhriti; Luthra, Kalpana (Frontiers in Immunology, 2019)
Studies conducted in animal models have suggested that membrane complement regulatory proteins play an important role in the pathophysiology of coronary artery disease (CAD). In this study, a total of 100 individuals, with stable CAD and 100 healthy controls, both groups predominantly male, were recruited. We evaluated the plasma levels of complement regulatory proteins (Cregs) CD35, CD46, CD55, and CD59 and their surface expression on granulocytes, lymphocytes, and monocytes by flow cytometry. The mRNA expression of these Cregs in total leukocytes was determined by quantitative PCR. The soluble forms of Cregs, C3c, Mannose binding protein-associated serine protease 2 (MASP-2), Platelet activating factor-acetyl hydrolase (PAF-AH), and inflammatory cytokines were quantified by ELISA. High plasma levels of C3c, indicative of complement activation, in addition to significantly low levels of Cregs, were observed in CAD patients. A significantly lower expression of CD46 and CD55 on the surface of lymphocytes, monocytes, and granulocytes and higher surface expression of CD35 and CD59 on granulocytes (p < 0.0001) was seen in CAD patients as compared to healthy donors. The high expression of CD59 on granulocytes positively correlated with the severity of disease and may serve as a potential marker of disease progression in CAD.